Investigating the influence of the AIR learning model on eighth graders’ listening comprehension - Indrasari, Nunun; Lestari, Alifahmi Ayudia; Kurniawati, Dewi (Universitas Negeri Medan, 2025)
Listening is a difficult basic skill to learn a second language because things like bad classroom environment, student with different language abilities, and limited vocabulary can make it harder. This study examines the impact of the Auditory, Intellectual, and Repetition (AIR) learning model on the listening skills of eighth-grade students at a private junior high school in Bandar Lampung, Indonesia. Due to research ethics, we can refer to the school by its initials, SMP AH. This study employed a quasi-experimental design, comprising two classes: one experimental class: 8 Thariq, n=25; and one control class: 8 Usamah, n=25, both recruited using cluster random sampling techniques from the population of eighth-grade students at SMP AH. Data for the research were gathered by multiple-choice pre-test and post-test. The study’s finding demonstrated a significant improvement in listening skills within the experimental group, as indicated by a two-sided significance value of 0.018 (< α = 0.05). This result rejects the null hypothesis and confirms the effectiveness of the AIR model. The results of this study demonstrate that the AIR model can enhance listening abilities in EFL contexts, providing valuable insights for teachers and educators. Subsequent research ought to investigate the long-term impact of employing the AIR model and utilize larger samples. Keywords: Auditory, Intellectual, and Repetition (AIR) learning model; listening skill; quasi- experimental design; second language acquisition; EFL teaching.